The value of ammoniated molasses in beef cattle wintering rations - Richardson, D.; Smith, E.F.; Baker, F.H.; Cox, R.F.; McReynolds, K.L. (Kansas Agricultural Experiment Station, 2012)
Forty head of good quality Hereford heifer calves were purchased from near Pueblo, Colo. They were divided as equally as possible into four lots of 10 heifers each. The starting ration for each lot is shown in Table 12. These rations were calculated to contain the same protein equivalent and total digestible nutrients per lot. The amount of silage was increased as the experiment progressed and all lots received the same amount. All animals were fed the control ration about a week before starting the experiment. During the experiment, the animals were fed once daily during the morning. The concentrates and molasses were spread over the silage and mixed. Warm water was mixed with the molasses in cold weather to make handling and mixing easier. As a result of thorough mixing, no animal was able to eat more than its share of any ingredient. A mineral mixture of steamed bonemeal and salt was fed free choice. Water was available at all times.
Keywords: Beef; Ammoniated molasses; Gain; Feed efficiency